Entomonematologic studies of the agrocenoses of Ukraine as a source of identification of the factors of the potential biocontrol of plant insects - Kovtun, A.M. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2016)
Various crops and long-term plantings in Ukraine (Zhytomyr, Kiev, Chernihiv, Khmelnytskyi and Vinnytsia Regions) have been observed for the purpose of identification of the natural centers of entomopathogenic nematodes (EPN) of the genera Steinernema and Heterorhabditis (Nematoda: Rhabditida) — the natural regulators of the number of harmful insects. The reasons and conditions, determining the nature of EPN distribution have been analyzed (Steinernema, Heterorhabditis). The results of the nematologic analysis of 206 soil samples (and traps) had showed that 27 (13.1%) among them turned out to be positive concerning EPN. The conducted examinations of garden and field biocenoses have showed that they are occupied by entomopathogenic nematodes unevenly. On identification frequency, representatives steinernematidae representatives prevailed over heterorhabditis nematodes (55.6% against 44.4%).